Jews in East Norse Literature A Study of Othering in Medieval Denmark and Sweden - Adams, Jonathan (Religious Minorities in the North, 2022)
This book explores the portrayal of Jews and Judaism in medieval Danish and Swedish literary and visual culture. Drawing on over 100 manuscripts and incunabula as well as runic inscriptions and religious art, the author describes the various, often contradictory, images ranging from antisemitism and anti-Judaism to the elevation of Jews as morally exemplary figures. It includes new editions of 54 East Norse texts with English translations.